“For us, the Zone is alive”. An Overview of TV Documentaries on Stalkerism in Chernobyl - Pavesi, Diletta (Green Narratives, Ecology and Sustainability in Contemporary Television - Exploring Narrative Ecosystems, 2025)
The phenomenon of stalkerism – a form of illegal tourism, usually practised by young Ukrainians, within the Chernobyl Exclusion Zone – has received increasing attention in recent years. Not surprisingly, this interesting practice has been the focus of several television documentaries dealing with the complex legacy of Chernobyl. It could be argued that stalking allows a traditional format such as documentary to develop an adventurous eco-narrative about the post-Chernobyl disaster. However, while the illegal exploration of the zone has been the subject of numerous sociological and even philosophical studies, television texts on the same subject are still largely ignored. T he aim of this essay is an overview and comparison of a number of recent television documentaries on dark tourism and stalking in Chernobyl. In particular, I will focus on the following titles available on Amazon Prime Chernobyl’s Café (2016) by Mike Baudoncq, The Zone: Post Atomic Journey (2018) by Pierpaolo Mittica and Alessandro Tesei, and Stalking Chernobyl: Exploration After Apocalypse (2020) by Iara Lee. Even though they deal with the same environmental and human issues, these three films have distinctive features. Chernobyl’s Café, for example, examines the resurrection of the ghost town, paying particular attention to the presence of a traditional café in the heart of the Exclusion Zone. The Zone deliberately combines the realistic account of a five-day trip by a group of young Ukrainians with fictional and highly melodramatic interludes. Stalking Chernobyl explores the underground culture of stalking from a political point of view, as is often the case in the films of activist filmmaker Iara Lee.